Application Various Sources of Organic Matter in the Cultivation of Chrysanthemum Plants as Cut Flowers - Arjana, I Gusti Made; Rudianta, I Nyoman; Sudewa, Ketut Agung (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
To enhance the intensity of chrysanthemum cultivation across different regions, further investigation is required regarding implementing suitable technology. This technology should be developed using local resources specific to chrysanthemum flowers to enhance their quality and value. Additionally, it should leverage readily applicable resources that align with farmers' capabilities, ultimately leading to a substantial increase in income. This study aims to acquire diverse organic materials suitable for chrysanthemum production in specific locations to examine the impact of different dosages on enhancing quality outcomes. The research methodology employed in this study is a Nested Experiments approach with a Random Design of Factorial Groups. Three types of organic sources are commonly utilized, namely: 1. organic matter derived from rasamala leaf litter (S), and 2. Chrysanthemum harvest residue (P). The study focuses on the effects of Chrysanthemums (P) and hydroponic media residue (H) on different types of organic matter with varying doses. The doses are nested within the different sources of organic matter. The findings indicated that the application of different sources of organic matter did not have statistically significant effects on the investigated variables, except the blossom diameter (cm), which exhibited a significant impact. The impact of different doses on the organic matter of various types of leaf litter had a notable influence on all observed variables. Specifically, a dose of 15 tons ha-1 resulted in the highest yield of economic flowers, with a fresh weight of 89.93 g. This represented a 17.01% increase compared to the lowest yield observed at a dose of 5 tons ha-1, which yielded 74.63 g. The relationship between different doses of organic matter remaining from chrysanthemum harvest and various observed variables was statistically significant. Specifically, a dose of 6 tons ha-1 resulted in the highest fresh weight yield of economically valuable flowers, measuring 94.89 g. This yield was 19.89% higher than the lowest yield observed with a dose of 2 tons ha-1, which measured 76.02 g. The impact of different doses on various types of organic matter in hydroponic media does not substantially influence all observable variables except for blossom diameter, which demonstrates a notable effect.